Influence of CRHR1 Polymorphisms and Childhood Abuse on Suicide Attempts in Affective Disorders: A GxE Approach - Ludwig, Birgit; Kienesberger, Klemens; Carlberg, Laura; Swoboda, Patrick; Bernegger, Alexandra; Koller, Romina; Wang, Qingzhong; Inaner, Michelle; Zotter, Melanie; Kapusta, Nestor D.; Haslacher, Helmuth; Aigner, Martin; et al. (Frontiers in Psychiatry, 2018)
Background: Previous studies have shown that the hypothalamus-pituitary-adrenal-axis (HPA-axis) is closely involved in the development of affective disorders. Given that early life events are also linked to dysregulation of the same system, there might be an association between childhood adversities and suicidal behavior in affective disorders, moderated by HPA-axis genes. We aimed to investigate a potential association between childhood trauma and previous suicide attempts in affective disorder patients, moderated by variants of the corticotropin-releasing hormone receptor 1 (CRHR1) gene. Methods: The current pilot study is part of an ongoing study on suicidal behavior in affective disorders (VieSAD). Two hundred fifty eight Caucasian affective disorder patients were assessed at the Department of Psychiatry and Psychotherapy of the Medical University Vienna and the Karl Landsteiner University for Health and Science. An assemblage of psychiatric interviews was performed (e.g., SCAN, HAMD, SBQ-R, CTQ) and DNA samples of peripheral blood cells were genotyped with TaqMan® SNP Genotyping Assays (rs7209436, rs4792887, rs110402, rs242924, and rs242939). Results: Neither genetic, nor haplotypic associations between CRHR1 polymorphisms and previous suicide attempts could be established for the present sample. Using a binary logistic regression model, significant gene-environment-interactions were found for the single nucleotide polymorphisms (SNPs) rs7209436 and rs110402, reflecting the impact of childhood trauma and CRHR1 polymorphisms on previous suicide attempts. Limitations: A larger sample size will be required to ultimately elucidate the link between childhood trauma and the HPA axis in suicidal behavior. Conclusion: This pilot study presents promising gene-environment-interaction findings in affective disorder patients with a history of suicide attempts.